Consumer knowledge about quality labelling concepts linked to family farming: Conhecimento sobre os conceitos de selos de qualidade vinculados à agricultura familiar - Groot, Etiénne (Programa de Pós-graduação em Desenvolvimento, Agricultura e Sociedade da Universidade Federal Rural do Rio de Janeiro (CPDA/UFRRJ), 2020)
Family farming is challenged by participating in Long Supply Chains. In this context, production processes must be communicated to the market through quality labels. The product’s added value increases when concepts related to the labels are known by consumers. The objective of this work was to evaluate consumers’ knowledge about quality labeling concepts, in Dracena (São Paulo State). For this, 257 personal interviews were conducted with the help of a structured questionnaire, between April and June 2018. The results indicate that 1/3 of consumers are unaware of organic farming and just over half are unaware of family farming concepts. Quilombo and fair-trade products are virtually unknown in Dracena. There was a positive relationship between educational attainment levels and knowledge of family farming and organic products. In conclusion, the work has shown the need for an extensive and continuous consumer information campaign on quality labelling.Keywords: Family Farming Identification Label (Sipaf); Brazilian Quilombo Label; FairTrade Label; Brazil Organic Product Label; Long Supply Chain.GROOT, Etiénne. Conhecimento sobre os conceitos de selos de qualidade vinculados à agricultura familiar. Estudos Sociedade e Agricultura, v. 28, n. 1, p. 136-155, fev. 2020.Submitted on October 7, 2019.Accepted on January 8, 2020.